Thyroid function in children and adolescents after combined therapy of Hodgkin disease - R. I. Feoktistov; Y. G. Abugova; Y. Y. Dyakonova; O. V. Makarova; N. V. Myakova (Онкогематология, 2014)
Thyroid diseases, especially hypothyroidism, are among the most frequent endocrine complications in patients with Hodgkin lymphoma whohave received neck irradiation. Thyroid function was evaluated in 34 patients (11 males and 23 females) after combined chemo radiotherapyof Hodgkin lymphoma according to modified DAL-HD-90M and GPOH-HD-2002 protocols. The median age was 15.9 years (range 5–18 years), the median time from the end of therapy was 1.08 years (range 1 month–4.9 years). 33 patients received radiotherapy to the neck region: 12 children — 20 Gy, 9 — 25 Gy, 10 — 30 Gy, 2 — 35 Gy. These patients were investigated by clinical examination, thyroid ultrasound and thyroid function tests. Thyroid abnormalities were detected in 4 of 21 patients who received 20–25 Gy (1 case of autoimmune thyroiditis and 3 cases of subclinical hypothyroidism) and in 3 of 12 patients who received 30–35 Gy (2 cases of autoimmune thyroiditis and 1 case of subclinical hypothyroidism). Autoimmune thyroiditis also developed in patient who received only 35 Gy mediastinum irradiation. Age, sex, follow-up time, irradiation dose were not significant factors in the thyroid dysfunction development. Thyroid examination must be obligatory part of the follow-up examination of patients with Hodgkin lymphoma.